PERAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATANBAGI PASIEN RAWAT INAP PADA RSUD dr. SOEBANDI JEMBER - Nely Supeni; Ahmad Sauqi (STIE Mandala Jember, 2016)
Purpose of this study is to determine the level of satisfaction of patients who had undergone hospitalization in dr. Soebandi Jember well as participants BPJS-Health as well as non BPJS health insurance participants.The data used in this study are primary data and secondary data. The samples used as many as 120 respondents. 60 respondents to respondents who had hospitalization in dr. Soebandi Jember as participants BPJS-Health and 60 for respondents who had hospitalization in dr. Soebandi Jember as non BPJS health insurance participants. The data analysis is done by non-parametric statistical tests, particularly the Chi Square test or chi-square test were symbolized by